Fibronectin Modulates the Expression of miRNAs in Prostate Cancer Cell Lines - Martinucci, Bruno; Cucielo, Maira Smaniotto; Minatel, Brenda Carvalho; Cury, Sarah Santiloni; Caxali, Gabriel Henrique; Aal, Mirian Carolini Esgoti; Felisbino, Sergio Luis; Pinhal, Danillo; Carvalho, Robson Francisco; Delella, Flávia Karina (Frontiers in Veterinary Science, 2022)
Prostate cancer (PCa) is a significant cause of cancer-related deaths among men and companion animals, such as dogs. However, despite its high mortality and incidence rates, the molecular mechanisms underlying this disease remain to be fully elucidated. Among the many factors involved in prostate carcinogenesis, the extracellular matrix (ECM) plays a crucial role. This ECM in the prostate is composed mainly of collagen fibers, reticular fibers, elastic fibers, proteoglycans and glycoproteins, such as fibronectin. Fibronectin is a glycoprotein whose dysregulation has been implicated in the development of multiple types of cancer, and it has been associated with cell migration, invasion, and metastasis. Furthermore, our research group has previously shown that fibronectin induces transcriptional changes by modulating the expression of protein coding genes in LNCaP cells. However, potential changes at the post-transcriptional level are still not well understood. This study investigated the impact of exposure to fibronectin on the expression of a key class of regulatory RNAs, the microRNAs (miRNAs), in prostate cancer cell lines LNCaP and PC-3. Five mammalian miRNAs (miR-21, miR-29b, miR-125b, miR-221, and miR-222) were differentially expressed after fibronectin exposure in prostate cell lines. The expression profile of hundreds of mRNAs predicted to be targeted by these miRNAs was analyzed using publicly available RNA-Sequencing data (GSE64025, GSE68645, GSE29155). Also, protein-protein interaction networks and enrichment analysis were performed to gain insights into miRNA biological functions. Altogether, these functional analyzes revealed that fibronectin exposure impacts the expression of miRNAs potentially involved in PCa causing changes in critical signaling pathways such as PI3K-AKT, and response to cell division, death, proliferation, and migration. The relationship here demonstrated between fibronectin exposure and altered miRNA expression improves the comprehension of PCa in both men and other animals, such as dogs, which naturally develop prostate cancer.